Modeling the intense 2012–2013 dense water formation event in the northwestern Mediterranean Sea: Evaluation with an ensemble simulation approach. Issue 2 (20th February 2017) - Waldman, Robin; Somot, Samuel; Herrmann, Marine; Bosse, Anthony; Caniaux, Guy; Estournel, Claude; Houpert, Loic; Prieur, Louis; Sevault, Florence; Testor, Pierre
Abstract: The northwestern Mediterranean Sea is a well‐observed ocean deep convection site. Winter 2012–2013 was an intense and intensely documented dense water formation (DWF) event. We evaluate this DWF event in an ensemble configuration of the regional ocean model NEMOMED12. We then assess for the first time the impact of ocean intrinsic variability on DWF with a novel perturbed initial state ensemble method. Finally, we identify the main physical mechanisms driving water mass transformations. NEMOMED12 reproduces accurately the deep convection chronology between late January and March, its location off the Gulf of Lions although with a southward shift and its magnitude. It fails to reproduce the Western Mediterranean Deep Waters salinification and warming, consistently with too strong a surface heat loss. The Ocean Intrinsic Variability modulates half of the DWF area, especially in the open‐sea where the bathymetry slope is low. It modulates marginally (3–5%) the integrated DWF rate, but its increase with time suggests its impact could be larger at interannual timescales. We conclude that ensemble frameworks are necessary to evaluate accurately numerical simulations of DWF. Each phase of DWF has distinct diapycnal and thermohaline regimes: during preconditioning, the Mediterranean thermohaline circulation is driven by exchanges with the Algerian basin. During the intense mixing phase, surface heat fluxes trigger deep convection and internal mixing largely determines the resulting deep water properties. During restratification, lateral exchanges and internal mixing are enhanced. Finally, isopycnal mixing was shown to play a large role in water mass transformations during the preconditioning and restratification phases. Key Points: NEMOMED12 is able to reproduce a realistic deep water formation event in 2012–2013 Ocean internal variability modulates half of the deep water formation area but it impacts marginally the integral deep water formation rate An ensemble simulation framework is necessary to evaluate accurately deep water formation in numerical ocean models